Collective mental time travel: Creating a shared future through our shared past. (July 2016) - Merck, Clinton; Topcu, Meymune N; Hirst, William
We connect two areas of research: psychological research on mental time travel as a way of understanding memory and the interdisciplinary work on collective memory. For individuals, remembering the personal past and imagining the personal future are closely related. We explore whether the link can extend to the collective realm. We review two recent studies that support this hypothesis and outline questions that should be addressed by future research. We conclude by addressing the relations between memory, simulation, and group identity.